Advances in the Development of Microbial Double-Stranded RNA Production Systems for Application of RNA Interference in Agricultural Pest Control - Guan, Ruobing; Chu, Dongdong; Han, Xinyi; Miao, Xuexia; Li, Haichao (Frontiers in Bioengineering and Biotechnology, 2021)
RNA interference (RNAi) is a valuable and revolutionary technology that has been widely applied in medicine and agriculture. The application of RNAi in various industries requires large amounts of low-cost double-stranded RNA (dsRNA). Chemical synthesis can only produce short dsRNAs; long dsRNAs need to be synthesized biologically. Several microbial chassis cells, such as Escherichia coli, Saccharomyces cerevisiae, and Bacillus species, have been used for dsRNA synthesis. However, the titer, rate of production, and yield of dsRNA obtained by these microorganism-based strategies is still low. In this review, we summarize advances in microbial dsRNA production, and analyze the merits and faults of different microbial dsRNA production systems. This review provides a guide for dsRNA production system selection. Future development of efficient microbial dsRNA production systems is also discussed.